Effects of the Inclusion of Jump Exercises with and without External Overload in the Warm-Up on Physical Performance Parameters in Young Handball Athletes - Gómez-Álvarez, Nicolás (2019)
The aim of this study is to compare the effects of a warm-up with the application of loaded and unloaded jumps on the performance in speed, horizontal jumps and vertical jumps in youth handball players. The sample consists of 13 handball players from the city of San Carlos (16.2 ± 1.3 years). An experimental study with a randomized crossover design carried out. 3 different heating protocols applied, which involved running more dynamic stretching (RS), running, dynamic stretching and jumping (RSJ) and finally running, dynamic stretching and jumps loaded with 8% of your body weight (RSLJ). For the pre- and post-warming assessments, a countermovement jump test (CMJ), horizontal jump (HJ) and were used through a 20-meter timed to sprint test. The results show significant differences between pre- and post-test for the 3 groups in the SH (difference for CES: 0.09 ± 0.12; CESH: 0.12 ± 0.16 and EC: 0.07 ± 0.16), while only CES and CESH significantly improved the height in CMJ and sprint time of 20 meters (difference for CMJ: 2.95 ± 0.56 and 3.50 ± 0.73; and sprint 20 meters: 0.29 ± 0,31 and 0.20 ± 0.26, respectively). In conclusion, a warm-up that includes different types of jumps is effective in improving SH, CMJ and speed in 20 meters. More research needed to determine specific benefits of handheld loading jumps to improve physical performance.